Implementation of Object Recognition Based on Type of Vehicle Entering Main Gate - Hairol Nizam Mohd Shah; Mohd Zamzuri Ab Rashid; Zalina Kamis; Muhammad Nizam Kamarudin; Mohd Fairus Abdollah; Alias Khamis (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This project related to develop and implementation of object recognition based on type of vehicle entering the main gate to facilitate the employment data of vehicles entering according to the types of vehicles. Data for the number of vehicles in accordance with the types recorded. In completing this project, there are two algorithms used, the detection algorithm and classification algorithm. Vehicles will be classified by comparison in terms of it front light area and will be stored in three types of vehicles; sedan, multipurpose van or van, and four wheel drive. Wireless camera is mounted with 1.6 meters high on the pipe rod at the guard house as input for the processing algorithm. Vehicle image will be captured by a wireless camera and then processed to identify its type. Data for the type of vehicle and number of vehicles by type is shown through the Graphical User Interface (GUI). Inflow and outflow of vehicles can be monitored via the control unit (GUI) without human monitoring at the entrance.